2016
DOI: 10.3906/kim-1606-34
|View full text |Cite
|
Sign up to set email alerts
|

A novel ion-imprinted polymeric sorbent for separation and determination of chromium(III) species in wastewater

Abstract: A new chromium(III) ion-imprinted polymer (IIP) was prepared from a Cr(III)-nicotinate complex (template), acrylamide (functional monomer), and ethylene glycol dimethacrylate (cross-linking agent) using 2,2'-azobisisobutyronitrile as the radical initiator. IIP was characterised and used as a selective sorbent for the solid-phase extraction of Cr(III) ions. The conditions for dynamic separation of Cr(III) on IIP were optimised. Cr(III) ions are selectively retained on the sorbent in a pH range from 9 to 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…In recent years, solid phase extraction (SPE) has become one of the most popular techniques for the separation of chromium species, as it can be easily coupled with electrothermal atomic absorption spectrometry (ETAAS), inductively coupled plasma mass spectrometry (ICP-MS) or inductively coupled plasma optical emission spectrometry (ICP-OES). Although commercially available materials are often used as solid sorbents, there has been an increasing interest in recent years to design special, new materials that are characterized by high selectivity for a given analyte, e.g., functionalized graphene and carbon nanotubes [16], nanocomposites [17,18], nanoparticles [15,19] or ion imprinted polymers [20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, solid phase extraction (SPE) has become one of the most popular techniques for the separation of chromium species, as it can be easily coupled with electrothermal atomic absorption spectrometry (ETAAS), inductively coupled plasma mass spectrometry (ICP-MS) or inductively coupled plasma optical emission spectrometry (ICP-OES). Although commercially available materials are often used as solid sorbents, there has been an increasing interest in recent years to design special, new materials that are characterized by high selectivity for a given analyte, e.g., functionalized graphene and carbon nanotubes [16], nanocomposites [17,18], nanoparticles [15,19] or ion imprinted polymers [20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature has shown that Cr(III)-ion imprinted polymers were prepared using Cr(III) complexes with 2-methacryloylamidohistidine (MAH) [23], nicotinic acid [24], 8-hydroxyquinoline [25], 1,5-diphenylcarbazide [26] and ammonium pyrrolidinedithiocarbamate [27] as templates. The polymeric structure was mainly formed by the cross-linking of methacrylic acid [26], acrylamide [24,27] with ethylene glycol dimethacrylate [24,27] or divinylbenzene [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations